Keanekaragaman Hayati di Elmina Rainforest: Upaya Pelestarian Spesies Langka di Tengah Perubahan Iklim - Budiyanti Budiyanti; Agustina Rahayu Sianturi; Esra Silaban; Fadila Khoiri; Mahara Sintong; Ellfayeti Ellfayeti (Lembaga Pengembangan Kinerja Dosen, 2025)
Tropical rainforests play a vital role in maintaining global climate stability and supporting the world's biodiversity. This study was conducted in the Elmina Rainforest, Selangor, Malaysia, with the aim of examining the current state of biodiversity and the impact of climate change on rare species. The methods employed included direct observation, in-depth interviews, and literature review. The findings indicate that anthropogenic pressures such as deforestation, pollution, and the effects of climate change have accelerated ecosystem degradation in the Elmina Rainforest. Phenomena such as savannization, pollinator population decline, and phenological disruptions were clearly observed in the field. Although conservation efforts have been initiated, challenges such as limited resources and insufficient community participation remain significant barriers. This study recommends ecosystem-based adaptation and mitigation strategies, ex-situ conservation, and active community engagement as key components for the successful preservation of rare species amid climate change. These findings underscore the importance of a holistic and collaborative approach in ensuring the sustainability of urban tropical rainforests.